Crop-damaging temperatures increase suicide rates in India - Carleton, Tamma A (Proceedings of the National Academy of Sciences - PNAS, 2017)
More than three quarters of the world's suicides occur in developing countries, yet little is known about the drivers of suicidal behavior in poor populations. I study India, where one fifth of global suicides occur and suicide rates have doubled since 1980. Using nationally comprehensive panel data over 47 y, I demonstrate that fluctuations in climate, particularly temperature, significantly influence suicide rates. For temperatures above 20 °C, a 1 °C increase in a single day's temperature causes ∼70 suicides, on average. This effect occurs only during India's agricultural growing season, when heat also lowers crop yields. I find no evidence that acclimatization, rising incomes, or other unobserved drivers of adaptation are occurring. I estimate that warming over the last 30 y is responsible for 59,300 suicides in India, accounting for 6.8% of the total upward trend. These results deliver large-scale quantitative evidence linking climate and agricultural income to self-harm in a developing country.